2001
DOI: 10.1002/casp.643
|View full text |Cite
|
Sign up to set email alerts
|

The influence of psychosocial and environmental factors on children's independent mobility and relationship to peer frequentation

Abstract: The ®rst aim of this study was to investigate whether demographic characteristics of children (i.e. age, sex, birth order), mothers' psychosocial characteristics (i.e. fear of crime, neighbourhood relations, sense of community, perceived risk of traf®c) and environmental factors (i.e. living in a new/old neighbourhood, in a building with a condominium courtyard, near a park or in a private street) in¯uence the independent urban mobility of 7±12-year-old children. The second aim was to verify whether children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
158
3
15

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(181 citation statements)
references
References 9 publications
5
158
3
15
Order By: Relevance
“…For example, a recent review found that reducing food prices and increasing the availability of healthy choices in high school cafeterias and vending machines resulted in increased purchase of the targeted foods, and improving the quality of the food served at school resulted in decreased fat intake. 13 The limited published empirical studies related to children's physical activity or mobility within their neighbourhood suggest that mother's neighbourhood ties, residing near parks and in a new neighbourhood, 15 amount of time spent outside, 16 access to public transport, parks or sports grounds and other facilities, 16,17 safe pedestrian and cycling conditions 17 and neighbourhood crime rates 18 may be important. While there is some evidence that supportive community environments are associated with physical activity, the impact of these environments on childhood obesity is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent review found that reducing food prices and increasing the availability of healthy choices in high school cafeterias and vending machines resulted in increased purchase of the targeted foods, and improving the quality of the food served at school resulted in decreased fat intake. 13 The limited published empirical studies related to children's physical activity or mobility within their neighbourhood suggest that mother's neighbourhood ties, residing near parks and in a new neighbourhood, 15 amount of time spent outside, 16 access to public transport, parks or sports grounds and other facilities, 16,17 safe pedestrian and cycling conditions 17 and neighbourhood crime rates 18 may be important. While there is some evidence that supportive community environments are associated with physical activity, the impact of these environments on childhood obesity is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Segundo , as experiências infantis no espaço urbano, geralmente, são mediadas pelos adultos ou por meios que afastam a criança da experiência real e corporal nesses ambientes, como quando estão dentro de automóveis. Dados contrários também são encontrados: as percepções de pais e fi lhos sobre as rodovias e ruas como sendo seguras estão associadas à maior frequência de atividades físicas por crianças e jovens (de 8 a 9 anos e 13 a 15 anos) (CARVER et al, 2010), assim como as mães que se sentem pertencentes à comunidade, as quais conhecem e se relacionam com seus vizinhos, permitem que seus fi lhos transitem pelo bairro (PREZZA et al, 2001).…”
Section: Métodos E Resultados Dos Estudos Sobre Mobilidade Da Criançaunclassified
“…Quais os efeitos das práticas de restrição do uso de espaços externos para o seu desenvolvimento físico, motor, cognitivo e social da criança? (PREZZA et al, 2001;O'BRIEN et al, 2000;KYTTÄ, 1997;. Kyttä (1997) e Neto e Malho (2004) citam que o desenvolvimento da criança não pode se restringir ao espaço da sua casa, ao quintal e ao playground, sendo que há uma vizinhança, um bairro ao redor com possibilidades de interações (affordances) a serem estabelecidas pela criança.…”
Section: Introductionunclassified
See 2 more Smart Citations